A Study on the Effect of Ladle Structures and Stirrer Positions on the Internal Flow Field in the Hot Metal Desulfurization Process - Lifei Wang; Qingchun Yu; Shubiao Yin; Guozhi Wang; Songlai Zhang (Metals)
The geometry of the ladle bottom and the position of stirring paddles during hot metal stirring significantly influence hydrodynamic characteristics, thereby affecting desulfurization efficiency. Water model experiments and hydrodynamic simulations were conducted to investigate the effects of ladle structures and stirrer positions on the flow field and mixing characteristics in hot metal desulfurization. The results indicate that ladles with a spherical-bottom structure effectively reduced the “dead zone” volume in the hot metal flow. In the water model tests, the mixing time for the spherical-bottom ladle was reduced by 22.5% and 20% at different stirring paddle speeds compared to the flat-bottom ladle, facilitating the better dispersion of the desulfurization agents. The hot metal flow velocities in all directions were also superior in spherical-bottom ladles. Under identical conditions, eccentric stirring generated shallower and broader vortices, with the vortex center offset from the stirring shaft axis, thereby minimizing the risk of “air entrainment” associated with high-speed central stirring. During eccentric stirring, the flow-field distribution was uneven, and the polarization of the stirrer was observed in the water model, whereas central stirring revealed a more uniform and stable flow field, reducing the risk of paddle wear and ladle wall erosion. Central stirring exhibits distinct advantages in the desulfurization process, whereas eccentric stirring is exclusively applicable to metallurgical modes requiring a rapid enhancement of bottom flow and localized rapid dispersion of desulfurizing agents.